Effectiveness of animation media in enhancing empathy to prevent bullying behavior in madurese adolescents - Aini Kurrota; Rini Hapsari Puspita (BIO Web of Conferences)
Bullying is a major problem in schools, involving aggressive and intentional behavior against others. This study aimed to investigate the effectiveness of animated media in enhancing empathy among high school students as a preventive measure against bullying. The research was conducted at State Senior High School 2 Bangkalan–Madura, using a pretest-posttest control group design. Students with low empathy levels were chosen through purposive sampling. The empathy of these students was measured using The Perth Empathy Scale (PES) and the Interpersonal Reactivity Index (IRI). The study divided students into two groups: experimental group watched three animated videos about different types of bullying (physical, verbal, and relational), while the control group did not receive any intervention. The effectiveness of the animated videos was evaluated by comparing empathy levels before and after the intervention. The results showed that the experimental group had a slight increase in empathy, with an average N-Gain Score of 0.21, which is considered low. However, a statistical test showed a significant improvement in empathy in this group, with a Sig. (2-tailed) value of 0.001 < 0.05, indicating that the videos made a meaningful difference. The control group did not show any significant change. This study concludes that animated media can be an effective tool to enhance empathy among adolescents, although the effect was small. It suggests that animated videos could be used in educational and psychological practices to help develop empathy in adolescents, which is crucial for preventing bullying in schools.